MODAL SOSIAL DALAM MENGEMBANGKAN KREATIFITAS PEMANFAATAN SAMPAH PLASTIK MENJADI ECOBRICK DI SMP NEGERI 23 PEKANBARU - Rafiqurrahim '; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted with the aim of identifying social capital in developing creativity in using plastic waste into ecobricks at SMP Negeri 23 Pekanbaru. This research uses descriptive qualitative method. Data collection through observation, interviews and documentation techniques. The results of the research show that SMP Negeri 23 Pekanbaru has made efforts to develop creativity in using plastic waste into ecobricks, including development through curriculum, education and outreach as well as sales to consumers. SMP Negeri 23 Pekanbaru also faces obstacles, including the condition of students becoming lazy and tired, lack of direct communication with student parents, design obstacles in marketing ecobricks. Even though it is faced with existing obstacles, this ecobrick activity has the potential to continue to develop and provide significant benefits in utilizing waste. The social capital found in developing creativity in using plastic waste into ecobricks at SMP Negeri 23 Pekanbaru is that trust is formed between schools, students and parents because ecobricks are a very useful activity in saving the environment. Trust from consumers or partners is very important in developing ecobrick activities. Values and norms are things that must be maintained by students because they are things that are not written down and must be obeyed. If there is a violation, you will receive a warning. The network that exists at SMP Negeri 23 Pekanbaru towards students and parents is that there are well-established relationships and networks with consumers or partners in building cooperation to achieve common goals. Keywords: Social Capital, Utilization of Plastic Waste, Ecobricks.